Educating Chinese, Japanese, and Korean International Students: Recommendations to American Professors - Roy, Shelly R. (Journal of International Students, 2013)
This paper discusses the unique barriers and learning difficulties encountered by Chinese, Japanese, and Korean international students when they study at institutions of higher education in the US. These learning difficulties arise because of inability of some American professors to use discourse markers, summarize at the end of lectures, write key concepts on the blackboard, etc. (Cox & Yamaguchi, 2010; Huang, 2004; Huang & Brown, 2009; Lee & Carrasquillo, 2006). The author argues that by using emotional intelligence (Goleman, 1998), the creating mind (Gardner, 2007), and the respectful mind (Gardner, 2007), American professors institutions of higher education in the US can enhance the learning experiences of their international students.